Human Development from Middle Childhood to Middle Adulthood Growing Up to be Middle-Aged - Pulkkinen, Lea (Taylor & Francis, 2017)
This seminal work focuses on human development from middle childhood to middle adulthood, through analysis of the research findings of the groundbreaking Jyväskylä Longitudinal Study of Personality and Social Development (JYLS). The JYLS project, which began in 1968, has generated extensive publications over many years but this is the first comprehensive summary that presents the conceptual framework, the research design and methodology, and the findings. The study looks at the development over time of issues related to personality, identity, health, anti-social behavior, and well-being and is unparalleled in its duration, intensity, comprehensiveness and psychological richness. The thorough synthesis of this study illustrates that there are different paths to adulthood and that human development cannot be described in average terms. The 42-year perspective that the JYLS provides shows the developmental consequences of children's differences in socioemotional behavior over time, and the great significance of children's positive socioemotional behavior for their further development until middle age. Not only will the book be an invaluable tool for those considering research methods and analysis on large datasets, it is ideal reading for students on lifespan courses and researchers methodologically interested in longitudinal research.